Faktor Internal dan Eksternal terhadap Return Saham - Rizqi Akbar; Dedi Suselo (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Stock returns along with the company's external and internal factors are examined to determine whether there is an influence between the two. The independent variables in this study are ROE (return on equity), DER (debt to equity ratio), CR (current ratio), and PER (price earning ratio) which are internal factors while external factors use inflation and SBI interest rates. The study was conducted using a quantitative method of panel data analysis. A purposive sampling strategy was used to select 15 manufacturing companies in the consumer goods industry sector based on certain criteria sourced from the Indonesia Stock Exchange (IDX) between 2017 and 2020. The data used in this study is secondary data. Eviews 10 is used to test the data under study. The results of this analysis indicate that simultaneously internal and external factors have a significant impact on stock returns. Meanwhile, if viewed respectively, DER, CR, and PER have a significant positive effect on stock returns but not with ROE, inflation, and interest rates. Keywords: stock returns, ROE, DER, CR, PER, inflation, SBI interest rate